HUBUNGAN WELAS ASIH DIRI DENGAN CITRA TUBUH PADA REMAJA DI SMA NEGERI 2 SEMARAPURA - Erismadewi, Pande Putu Ayu; Swedarma, Kadek Eka; Antari, Gusti Ayu Ary (Coping: Community of Publishing in Nursing; Vol 10 No 1 (2022): Februari 2022DO - 10.24843/coping.2022.v10.i01.p06, 2022)
Pressure on body image as a psychosocial problem that was often experienced by adolescents. Low or negative body image may caused a negative impact on adolescent's growth. Self-compassion is one of the factors that influence body image. Self-compassion can increase positive thinking about acceptance of appearance and positive thinking about oneself so that it is expected to form a high or positive body image in adolescents. This research aims to determine the relationship between self-compassion and body image in adolescents in SMA Negeri 2 Semarapura. The research method was used quantitative with a cross-sectional study design. Self-compassion data collection was analyzed by using the Self-Compassion Scale (SCS) questionnaire and the body image was analyzed by using the Multidimensional Body Self Relational Questionnaire-Appearance Scale (MBSRQ-AS) questionnaire. The results of the univariate analysis showed that most adolescents has moderate self-compassion from 136 respondents (74.3%) and has a high body image from 106 respondents (57.9%). Data analysis was used Spearman Rank, it was found that there was a weak relationship with the direction of a significant positive relationship between self-compassion and body image of adolescents in SMA Negeri 2 Semarapura (p = 0.000; r = 0.325). Researchers recommend that schools and health workers be able to join, to create and support programs in reducing the psychological pressure of adolescents, especially in creating a positive body image through education on the importance of cultivating self-compassion in adolescents.